Pengaruh Return on Asset, Leverage, Ukuran Perusahaan terhadap Manajemen Laba dengan Kepemilikan Manajerial sebagai Variabel Moderating pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Dina Aulia; Kersna Minan; Listiorini Listiorini (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to examine and analyze the effect of return on assets, leverage, firm size on earnings management with managerial ownership as a moderating variable. The approach used in this research is a quantitative approach. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study used purposive sampling totaling 21 companies. Data collection techniques in this study using documentation techniques. The data analysis technique in this study used Moderating Least Square using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program.The results of this study prove that directly return on assets, leverage, firm size has no effect on earnings management, managerial ownership is not able to moderate the effect of return on assets, leverage, firm size has no effect on earnings management.